Odpowiedzi

Najlepsza Odpowiedź!
2009-10-12T19:13:29+02:00
X+ √6 = x√2 + √3 (podnieśmy wszystko do kwadratu, aby pozbyć się pierwiastków)

D∈R₊

x² +6 =2x² +3
-x²+3=0

∧(delta)
∧=b²-4ac = 0+12 =12
∧=12


x₁= -b-√∧/2a = -√12/-2 = √12/2= 2√3/2= √3 ∈D

x₂= -b +√∧/2a = √12/-2 = 2√3/-2 = -√3 ∉D

Rozwiazaniem jest x =√3

Pozdrawiam,
matteushq;)
2 1 2
2009-10-12T19:23:47+02:00
X+ √6 = x√2 + √3 | * kwadrat

x2 + 6 = 2x2 + 3
- x2 = -3
x2 = 3
x = √3

sprawdzenie

√3 + √6 = √3 * √2 + √3
√3 + √6 = √6 + √3
strona lewa = stronie prawej
1 1 1